2021
DOI: 10.1021/acsanm.1c00598
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale AgInTe2/Si Truncated Quasitetrahedrons for Heterostructured Photodetectors

Abstract: Group I−III−VI 2 semiconductors are promising for the fabrication of electronic and photoelectronic devices because of their tunable band gaps and intensive absorption in visible and near-infrared regions. Here, ternary AgInTe 2 nanostructures have been synthesized via a facilely designed solution-phase procedure at 240−280 °C from AgNO 3 and In(acac) 3 in oleylamine reacted with TeO 2 dissolved in 1-dodecanethiol. They illustrate truncated quasitetrahedrally geometrical shapes from the phosphine-free solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 58 publications
(113 reference statements)
1
22
0
Order By: Relevance
“…Another set of doublets located at 576.2 and 586.6 eV can further prove the existence of TeO 2 , which was probably caused by surface oxidation, in good agreement with its frequent occurrence for telluride in previous studies. 25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another set of doublets located at 576.2 and 586.6 eV can further prove the existence of TeO 2 , which was probably caused by surface oxidation, in good agreement with its frequent occurrence for telluride in previous studies. 25…”
Section: Resultsmentioning
confidence: 99%
“…Another set of doublets located at 576.2 and 586.6 eV can further prove the existence of TeO 2 , which was probably caused by surface oxidation, in good agreement with its frequent occurrence for telluride in previous studies. 25 To investigate the optoelectronic characteristics of the solution-grown ternary quasi-cube AgSbTe 2 nanostructures, a typical photodetector device was fabricated on a glass substrate with a slit between two adjacent parts of the indium tin oxide film. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I 4̅ 2 d ) IB-IIIA-VIA 2 is a group of ternary semiconductors. Their crystal structures are analogous with a double zinc blende or B3 structure (IIB-IVA) in which IIB atoms are replaced by IB and IIIA atoms with a ratio of 1:1. It is well-known that the IB-IIIA-VIA 2 compounds have been intensively investigated because of their various applications; for example, CuInSe 2 is a vital absorber layer material and gives an advantage to flexible thin-film solar cells with high conversion efficiencies of approximately 19%. CuInTe 2 has applications in photoluminescent and photovoltaic devices. , Furthermore, AgInTe 2 could be used for optoelectronic switching at higher frequencies and heterostructure-based photodetectors . More interestingly, numerous recent studies have shown that chalcopyrite compounds potentially exhibit promising thermoelectric (TE) materials with high values of figure of merit (ZT). Especially in Ag-based chalcopyrite semiconductive materials, the thermal conductivities of AgGaTe 2 and AgInTe 2 are relatively low compared to those of CuGaTe 2 and CuInTe 2 , leading to them being widely studied for application in TE materials. , AgGaTe 2 with varying Ag content has a beneficial ZT of 0.8 at 850 K .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the optical band gap value is calculated by plotting ( αhν ) 2 versus hν ( α = absorption coefficient, h = Planck's constant, and ν = frequency). 39 By extrapolating the linear portion of the plot (the inset in Fig. 4a), a direct optical band gap is determined to be 1.25 eV.…”
mentioning
confidence: 99%